Variasi Genetik Gen Myostatin Ekson 3 pada Sembilan Bangsa Kambing Lokal di Indonesia - Rissa Herawati Ginting; Achmad Farajallah; Dyah Perwitasari Farajallah; Aron Batubara (Institut Pertanian Bogor, 2017)
Myostatin gene plays a role in helping to control the growth and development of muscle tissue. Identification of genetic diversity in nine local goat breeds in Indonesia has done. The aim of this study was to obtain information myostatin gene diversity of exon 3 in local goats in Indonesia. The total of 10 samples was selected from 80 samples of goat's blood collected comprising each sample of the population of goats breeds, i.e., Samosir, Muara, Kacang, Costa, Peranakan Etawah, Boerawa, Gembrong, Boer, and Boerka goats. The gene diversity and nucleotide base changes were identified by using polymerase chain reaction (PCR) and sequencing techniques. The analysis showed that there is eight variant identified in appropriate with those found in sequencing results. Deletion variations were found in Costa and Samosir goats in T552- and G560-. Substitution variations were found in Gembrong (A7C & A11T), Peranakan Etawah (T10A & A11T), Burawa (T10A & A11T), Muara (A11T), Samosir (A11T), and Boerka (A182T, T437A, T439A, & A445G). Variations on the chromatogram peak overlapping contained in the base position to 13. Analysis of variance showed that there was a special mutation in exon 3 that affects the amino acid tyrosine into lysine. Variants were found in nine goat breeds associated with phylogenetic and genetic distance of goats, Boerka goat has the highest level of genetic variation, it indicated that Boerka goat was crossbreed